Inovasi alat press dan cetak tahu pada UKM tahu Ngaran - Prima Astuti Handayani; Widhi Mahatmanti; Sarwi Asri; Masni Maksiola; Raihan Madanii; Galih Muhammad Falefi; Mohamad Fiqih Sa'ari (Universitas Muhammadiyah Mataram, 2025)
Abstrak UKM Tahu Ngaran berlokasi di Kelurahan Pakintelan Kecamatan Gunungpati Semarang dan memproduksi tahu secara mandiri mulai tahun 2002. Tahu Ngaran setiap proses produksi membutuhkan 10 kg kedelai dan menghasilkan 6 peniris tahu, dimana setiap tahu dijual dengan harga Rp. 40.000,- per peniris. Tahu Ngaran setiap harinya mampu produksi 5-10 kali proses produksi, yang dipasarkan ke daerah Bangetayu Semarang. Permasalahan mitra yaitu 1) UKM belum menggunakan teknologi, 2) Alat cetak tahu masih terbuat dari anyaman bambu, 3) Pemasaran tahu belum menggunakan kemasan. Solusi yang ditawarkan meliputi; 1). Pembuatan alat press dan cetak tahu terbuat stainless steel, 2). Tahu dikemas sehingga produk tetap higienis dan pemberian label kemasan. Tujuan dari kegiatan PkM meningkatkan produktivitas dan higienitas tahu pada Tahu Ngaran, sehingga dapat meningkatkan kesejahteraan perajin serta masyarakat Pakintelan Kecamatan Gunungpati pada umumnya. Metode yang dilakukan meliputi 1). koordinasi tim dengan mitra pelaksanaan kegiatan PkM; 2). Sosialisasi proses pembuatan tahu yang higienis ;3). Fasilitasi alat press dan cetak tahu berbahan stainless steel ;4). Pembuatan label kemasan; 5). Praktek penggunaan alat press dan cetak tahu hasil PkM; 6). Pendampingan; 7). Evaluasi pelaksanaan dan keberlanjutan program. Hasil kegiatan PkM yaitu modifikasi alat press dan cetak tahu berbahan stainless steel, sehingga mudah dibersihkan dan mempercepat proses cetak tahu. Alat cetak tahu sebelumnya menggunakan pemberat batu yang membutuhkan waktu sekitar 35 menit, sedangkan dengan alat hasil PkM dapat mempersingkat waktu menjadi 15 menit. Dengan demikian dengan alat hasil PkM dapat meningkatkan produksi Tahu Ngaran. Kata kunci: tahu; cetak tahu; higienis; stainless steel. AbstractUKM Tahu Ngaran, located in Pakintelan Village, Gunungpati District, Semarang, has been independently producing tofu since 2002. Each production cycle requires 10 kg of soybeans and yields six trays of tofu, with each tray sold for Rp. 40,000. Tahu Ngaran conducts 5 to 10 production cycles per day, distributing its products to the Bangetayu area in Semarang. Several challenges have been identified in the production process: (1) the absence of modern technology adoption, (2) the use of woven bamboo as the primary material for tofu molding equipment, and (3) the lack of proper packaging in the marketing strategy. To address these issues, the proposed solutions include: (1) the development of stainless steel tofu pressing and molding equipment to enhance hygiene and efficiency and (2) the implementation of hygienic packaging with labeling to improve product quality and marketability. This community program (PkM) aims to enhance the productivity and hygiene of tofu production at Tahu Ngaran, thereby contributing to the well-being of tofu artisans and the broader community in Pakintelan Village, Gunungpati District. The methodology employed in this study consists of several stages: (1) coordination between the research team and SME partners, (2) dissemination of information on hygienic tofu production processes, (3) provision of stainless steel tofu pressing and molding equipment, (4) development and application of product labeling, (5) training in the use of the improved tofu press and mold, (6) continuous mentoring, and (7) evaluation of program implementation and sustainability. The outcomes of this PkM initiative include the successful modification of tofu pressing and molding equipment using stainless steel, which facilitates cleaning and enhances production efficiency. The traditional tofu molding process relied on stone weights, requiring approximately 35 minutes per cycle. In contrast, the newly developed equipment reduces processing time to 15 minutes. This technological improvement significantly increases production capacity and contributes to the overall enhancement of the tofu manufacturing process at Tahu Ngaran. Keywords: tofu; tofu mold; hygienic; stainless steel.